Implementation Of Dynamic Governance Concept In Regional Government Of Siak Regency - Mayarni Mayarni (Iapa Proceedings Conference, 2018)
Environmental change encourages the birth of a contextual policy (adaptive policy) that is not only a passive reaction to external pressure but also a proactive approach to innovation, contextualization, and execution. New ideas also result in a contextual policy (adaptive policy) can be executed and generate dynamic governance. Boon and Geraldine formulated Dynamic Governance as "how these choosen paths, policies, institutions, and structures adapt to an uncertain and fast changing envinronment so that they are relevant and effective in achieving the long-term desired outcomes of society. Public administration reform is closely linked to the concept of dynamic governance, because public administration reforms are oriented towards changes among others in the implementation of public policy. Dynamic Governance is a concept to maintain and develop the existence of a government / organization to survive (survive) to face rapid and uncertain global change. Other government / organizational organizations should not be static, successes of policies, strategies, and programs in progress or past does not guarantee future success. Therefore it is necessary spirit / dynamics to always adjust policies, strategies, and programs with future developments through thinking ahead, thinking again, and thinking across. The results show that the application of dynamic governance concept in Siak Regency has been done with good result. It is proved that throughout the year 2017, as many as 24 awards and achievements they achieve both at the level of Riau Province and at the national level. Of the 24 awards, it can be said that every month two awards are achieved in the former Malay kingdom of Islam. Based on the achievements achieved by the local government of Siak Regency shows the ability of the government to adjust the policy to the rapid and uncertain global environment changes so that the established objectives can be achieved as proof that the application of dynamic governance concept has been done by Siak Regency Government very well.